2017
DOI: 10.1002/jcla.22363
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of peripheral blood microRNA detection in evaluation of SOX regimen as neoadjuvant chemotherapy for gastric cancer

Abstract: Patients with GC at advanced stages had aberrant miRs expressions. Detection of miR-145 and miR-185 expression may assist to predict effectiveness and adverse effects of SOX regimen as neoadjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Although surgery is considered as the mainstay of curative treatment, more than 50% patients with locally advanced GC recur even after complete resection [10]. Accordingly, investigators have demonstrated that neoadjuvant chemotherapy has been widely used in the treatment of advanced GC [11]. However, the effectiveness of neoadjuvant chemotherapy in patients with GC remains unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…Although surgery is considered as the mainstay of curative treatment, more than 50% patients with locally advanced GC recur even after complete resection [10]. Accordingly, investigators have demonstrated that neoadjuvant chemotherapy has been widely used in the treatment of advanced GC [11]. However, the effectiveness of neoadjuvant chemotherapy in patients with GC remains unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence uncovered non‐coding RNAs (ncRNAs), including microRNAs (miRNAs), long non‐coding RNAs (lncRNAs), circular RNAs (circRNAs), and transfer RNAs (tRNAs), could be used in GC diagnosis and prognosis . Some altered ncRNAs played a crucial role in the regulation of malignant phenotypes of tumor .…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al identified that tiRNA‐5034‐GluTTC‐2 might be responsible for a marker for GC diagnosis. Tan et al established that detection of miR‐145 and miR‐185 might be helpful for predicting adverse reactions and effectiveness of SOX regimen against GC . Recent reports illustrated that circ_0067582, circ_0005758, circ_0000467 and circ_0000181 could suggest a role in GC carcinogenesis, and be potential indicators in screening GC .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations